2020
DOI: 10.1186/s40104-020-00440-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the glutathione redox system during the weaning transition in piglets, in relation to small intestinal morphology and barrier function

Abstract: Background: Weaning is known to result in barrier dysfunction and villus atrophy in the immediate post-weaning phase, and the magnitude of these responses is hypothesized to correlate with changes in the glutathione (GSH) redox system. Therefore, these parameters were simultaneously measured throughout the weaning phase, in piglets differing in birth weight category and weaning age, as these pre-weaning factors are important determinants for the weaning transition. Low birth weight (LBW) and normal birth weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
2
12
0
Order By: Relevance
“…Our LMR revealed that an aggressive restriction of milk can increase PPE in calves, agreeing with increased PPE observed for feed restrictions in mature cows (Kvidera et al, 2017). Our results also highlighted a lag time (4-7 d) for the PPE response, which is in agreement with Degroote et al (2020). Those authors assessed PPE in the small intestine of weaned piglets and did not see a PPE increment until 5 d postweaning.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our LMR revealed that an aggressive restriction of milk can increase PPE in calves, agreeing with increased PPE observed for feed restrictions in mature cows (Kvidera et al, 2017). Our results also highlighted a lag time (4-7 d) for the PPE response, which is in agreement with Degroote et al (2020). Those authors assessed PPE in the small intestine of weaned piglets and did not see a PPE increment until 5 d postweaning.…”
Section: Discussionsupporting
confidence: 90%
“…Those authors assessed PPE in the small intestine of weaned piglets and did not see a PPE increment until 5 d postweaning. Degroote et al (2020) also showed a markedly induced oxidative damage to the intestinal mucosa that was closely in line with the PPE response for weaning. Perhaps, the Gln supplementation mitigated the potential increase in PPE by alleviating oxidative damage to the intestinal mucosa of weaning calves (Ji et al, 2019).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Weaning stress leads to the excessive production of oxygen free radicals, resulting in lipid peroxidation and damage to the structure and function of biofilm ( Cao et al, 2018 ; Degroote et al, 2020 ; Novais et al, 2021 ). A previous study reported that the exogenous addition of magnesium can alleviate the decrease of GSH-Px activity in mitochondria of premature aging mice caused by oxidative stress ( Villa-Bellosta, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intestine is not only the largest digestive and absorption organ in animals, but also the largest immune organ in the body, and early weaning can affect intestinal health [ 5 , 6 ]. At present, there are more studies on the effect of weaning on piglets’ intestines, mainly focusing on the intestinal barrier, intestinal permeability, and the structure and diversity of microbiota in the intestine [ 7 , 8 ]. Bile acids (BAs), as metabolites of intestinal microorganisms, can promote nutrient absorption and play an important role in the regulation of intestinal physiology, and they are of great interest as participants in the metabolic pathway of the “hepatic-intestinal cycle” in animals [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%